2007
DOI: 10.1259/bjr/16010686
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose measurement and risk estimation for paediatric patients undergoing micturating cystourethrography

Abstract: Micturating cystourethrography (MCU) is considered to be the gold-standard method used to detect and grade vesicoureteric reflux (VUR) and show urethral and bladder abnormalities. It accounts for 30-50% of all fluoroscopic examinations in children. Therefore, it is crucial to define and optimize the radiation dose received by a child during MCU examination, taking into account that children have a higher risk of developing radiation-induced cancer than adults. This study aims to quantify and evaluate, by means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 14 publications
3
22
0
Order By: Relevance
“…However, a disparity exists among these guidelines in terms of the imaging modality to be performed and the exact protocol to be followed [13,14]. MCUG has a number of disadvantages including invasive nature, radiation exposure, the risk of secondary infection and significant discomfort for the patient [22,23]. Previous studies have suggested that DMSA scanning can obviate the need for MCUG examination in infants and younger children presenting with first febrile urinary tract inection [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, a disparity exists among these guidelines in terms of the imaging modality to be performed and the exact protocol to be followed [13,14]. MCUG has a number of disadvantages including invasive nature, radiation exposure, the risk of secondary infection and significant discomfort for the patient [22,23]. Previous studies have suggested that DMSA scanning can obviate the need for MCUG examination in infants and younger children presenting with first febrile urinary tract inection [16].…”
Section: Discussionmentioning
confidence: 99%
“…A calibrated X ray machine Toshiba, model DRX-1603B was used under reproducible reference conditions to deliver a known absorbed dose to the TLDs. For the TLD and chamber irradiation, a polymethylmethacrylate (PMMA) calibration test bed was constructed having dimensions 30x30x10 cm 3 , which simulates the patient's lateral and backscatter conditions (Martin et al, 1998, Sulieman et al, 2007. The first PMMA slab was used to accommodate the TLD chips in an array of slots 10x10.…”
Section: Tl Dosimetrymentioning
confidence: 99%
“…The effective dose to the organs and tissues has been calculated using the methodology and tissue weighting factors reported at NCRP 122, 1995 andICRP 103, 2007, respectively. A computer program was developed, allowing calculation of the dose to 14 organs and tissues (Sulieman et al, 2007).…”
Section: Staff Dose Measurementmentioning
confidence: 99%
“…Voiding cystourethrography is considered the standard method in the evaluation of vesicoureteral reflux and malformations of the urethra and bladder (4) . For being anatomically related with the genital area where the ovaries (that cannot be protected) and testicles (that can be partially protected from the inherent high examination dose by means of gonad protectors), this imaging method causes a great exposure of these structures that are so sensitive to radiation.…”
Section: (10)mentioning
confidence: 99%
“…of the urinary tract and, according to reports in the literature, represents 30% to 50% of fluoroscopy studies performed in children (3,4) . The main indications for this imaging method are: evaluation of repeated urinary infections, vesicoureteral reflux and congenital abnormalities of the bladder and of the urethra.…”
mentioning
confidence: 99%